(untitled) (Research, Society and Development, 2021)
Introduction: Product advertisements influence the formation of new consumers, using the mobilization of their fantasies, forging a feeling of happiness when purchasing a certain product, becoming essential in the process of convincing parents, who are responsible for the purchase. Goal:To analyze the scientific evidence of parental relationship and media influence on children’s eating behavior. Methodology: This is a narrative literature review with a theoretical approach. The search for articles was performed in the following electronic databases: Scientific Electronic Library Online (SciELO), National Library of Medicine (PubMED) and Latin American and Caribbean Literature on Health Sciences Information (LILACS), using the descriptors in Portuguese and English: “Eating behavior”, “child”, “food”, duly registered in the Health Science Descriptors (DeCS) in a proposed time frame, between the years 2011 to 2021. Results: The research was subdivided into two categories which made up the discursive body of the text: Parental relationship and eating behavior in children and Implications of the media in children’s eating behavior. Final considerations: Therefore, parenting and the influence of the media have a great impact on the lives of children, who are in the learning process and become more fragile in relation to these factors.